KADAR PROTEIN DAN SIFAT ORGANOLEPTIK NUGGET RAJUNGAN DENGAN SUBSTITUSI IKAN LELE (Clarias gariepinus) (Protein Levels and Organoleptic Crab Nugget with Substitution Catfish (Clarias gariepinus) - Anas Ubaidillah; Wikanastri Hersulistyorini (Jurnal Pangan dan Gizi, 2010)
Crab meat (Second-grade) is a sort of meat produced by crab processing industry which has export quality. Crab meat (second-grade) used to a product which has value added but has not been optimal. One of effort to develop this product is substitute the crab meat with catfish meat into crab nugget product. Catfish is one source of animal protein which is cheaper but it has high nutrient. So the substitution is expected to be an affordable price of processed product. The research object is a product with a substitution crab nugget into catfish meat (Clarias gariepinus). The independent variables in this research were variations of substitution and dependent variable is the proportion of protein and flavor in crab nugget product. Chemical analysis is carried out quantitative analysis of protein and flavor. The design used completely randomized design in three replication. The results showed that there are effects of substitution catfish meat and crab meat on protein crab nugget product. While flavor of aroma, flavor and texture except color there are not effect on protein crab nugget product. The highest protein of crab nugget product is product with substitution L0: R100 is 10.06% while product with substitution L95: R5 has little protein about 8.15%. The result showed that favorite flavor of crab nugget product is a product which has substitution L65: R35 about 2.95 and substitution of product with L0: R100 has the smallest value about 2.56. Key words: crab nugget, protein, substitution catfish.